Thermoelectric Mini Portable Fridge with Wireless Temperature Monitoring - ghazali, Noor zuhairah; Mohd Shah, Nor Shahida; Kuamthab, Nor Elisya; Mohamad, Mahathir (Progress in Engineering Application and Technology, 2021)
To continue cooling food or medication during travel, people need a compact refrigerator that is easier to bring anywhere. Thus, the goal of this project is to build a Peltier thermoelectric mini-portable fridge, plus, the temperature can be monitored wirelessly. The fridge monitoring system consists of a DHT11 sensor, HC-05 Bluetooth module, LCD, and Arduino Uno. The Arduino cord is also programmed with minimal software called Arduino Real, which programs the Peltier module’s cooling temperature. The results show that when the time arises, the temperature decreases rapidly and the humidity fluctuated. The saturation point increases as the temperature of the air changes. Before it becomes saturated, cold air can carry less water vapor, and hot air can retain more water vapor before it becomes saturated. To maintain a low temperature in the fridge, which is a minimum of 7°C in this project, the supply needs to have sufficient power to the heat sink, the fans, and the Peltier module.